Contributions and Challenges of Public Health Social Work Practice during the Initial 2020 COVID-19 Outbreak in China. (23rd April 2022) - He, Longtao; Mu, Liping; Jean, Jason A; Zhang, Lei; Wu, Han; Zhou, Tian; Bu, He
Abstract: Social workers contributed significantly to the promotion of public and community health during the initial outbreak of COVID-19 in China. Based on a quasi-scoping review of articles on social work practice during that outbreak, this reflective article elucidates how social workers contributed in three chronological stages. In the early stage (late January and February 2020), social workers provided community services offered as part of the governmental structure (moderate information and resource provision); in the middle stage (March 2020), social workers provided services to vulnerable groups alongside supporting the quarantine strategy; and in the late stage (April 2020 onwards), their services were focused on recuperation and recovery after the national lockdown was lifted. In the meanwhile, several issues for public and community health social work as a profession in terms of how it was able to support anti-COVID-19 practices became clear, including a lack of independence and stability, the need for better flexibility and greater ability to act pragmatically and lack of professional agreement. This article aims to enlighten the development of a (re)emerging field—public health and community health social work in China in the wake of the COVID-19 pandemic. Abstract : In their response to the initial outbreak of COVID-19 in China, Chinese social workers were able to take their place on the international stage and share their experiences and knowledge with the rest of the world. Thus, we aim to examine the experiences of social workers during the initial outbreak of COVID-19 in China to promote public health. Based on a quasi-scoping review of articles on social work practice during the initial outbreak of COVID-19 in China, this reflective article elucidates how social workers contributed in different roles and focuses over three stages. Three suggestions are also made in terms of confronting the challenges arising in each stage: increase the independence and visibility of social work in the system, prioritise practice and flexibility over rigid procedures and increase professional collaborations and do away with disputes around the provision of community and public health social work services.